Monolith Dental Bridge by Soft Machining of Dried Ceramic Dough - Seesala, Venkata Sundeep; Vaidya, Pravin Vasudeo; Rajasekharan, Ragavi; Kumar Ojha, Atul; Jana, Subhodeep; Pal, Barnali; Dhara, Santanu (Frontiers in Dental Medicine, 2021)
All-ceramic fixed restorations are gaining popularity because of increased esthetic consciousness in the younger population. Monolith ceramic crowns and bridges are preferred to withstand masticatory loads where the availability of occlusal height is limited. Machining green blanks of ceramic with organic binders have been studied to reduce loss of final strength, cost, and wastage associated with milling partial sintered and sintered blanks. Notches on the surface/edge associated with green milling will disappear after sintering in contrast to sintered state machining where diamond polishing is essential. In this study, we explored a novel ceramic dough process to form a green body of alumina or 3 Mol% yttria-stabilized zirconium oxide (YSZ), and computer numerical control (CNC) machining was performed on the dried dough. Micro Computer Tomography analysis of the bridges after sintering revealed a negligible void volume, 0.06–0.08% of the total volume, with randomly dispersed voids. Precision analysis of the sintered bridges with respect to the reference file resulted in a deviation range of +0.56 to −0.79 mm, with negligible deviation on the cementation surface. The green machined surface had a roughness profile of 1.2–1.7 μm after machining and 2.2–2.4 μm after sintering, as revealed by 3D profilometry.